Clinicopathological and hysteroscopic study of endometrium in abnormal uterine bleeding - Guruvelli, P. Sandyarani; Atla, Bhagyalakshmi; Namballa, Uma; Shaik, Roohi Firdous; Peddireddy, Deepika; Gadamsetti, Tharuna Shravyya (International Journal of Research in Medical Sciences, 2025)
Background: Abnormal uterine bleeding (AUB) is defined as bleeding from uterus that is longer than usual (>7days), more than normal volume (>80ml/cycle) and varying in frequency. AUB is commonly seen in reproductive women and affects the quality of life. The study aims to compare the diagnostic accuracy of hysteroscopy correlated with histopathology in evaluation of pathology of endometrium in patients with AUB. Methods: The study was a cross sectional observational study with samples of Dilatation and Curettage, endometrial biopsies, conducted at NRI Institute of Medical Sciences, Visakhapatnam, in the Department of Pathology over a period of 24 months from July 2022 to June 2024 with sample size of 135 patients. Results: Among 135 cases, the predominant age group was perimenopausal comprising of 66 cases (48.88%). According to age wise distribution common bleeding pattern was menorrhagia in both reproductive and peri menopausal age group comprising of 39 cases and 47 cases. Post-menopausal bleeding was most common bleeding pattern in post-menopausal women comprising of 10 cases. Among the three age groups, structural causes were high comprising of 124 cases (91.85%) and non-structural causes constitute 11cases (8.14%).The commonest pattern was proliferative endometrium constituting 34.81% followed by secretory endometrium 30.37%, Hyperplasia without atypia 18.51%. Accuracy of Hysteroscopy with Histopathology was 94.44%. Conclusions: Hysteroscopy is a safe reliable and quick procedure in the diagnosis of cases with abnormal uterine bleeding, it should not replace tissue diagnosis, which remains the gold standard.